Effect of sex hormones on metabolic disturbances in menopausal women - Grycewicz, Joanna; Cypryk, Katarzyna (Menopause Review/Przegląd Menopauzalny, 2008)
Menopause is a consequence of ovarian hormonal function inhibition and is accompanied by a number of clinical symptoms resulting from the extrareproductive role of sex hormones. Sex hormones exert their effect through binding with a specific receptor. At present there are two types of oestrogen receptors coded by two different genes: type a (ERa) and type β (ERb). Although a and β oestrogen receptors have similar structure, they differ in the number and sequence of amino acids as well as in the distribution and density of particular types of the receptor in tissues. Receptors’ distribution is significantly decisive for the effect of oestrogens on particular tissues. The hormonal changes observed during menopause are the cause of intensified neurovegetative symptoms, atrophic changes in oestrogen-dependent tissues and numerous metabolic disturbances. The paper discusses extrareproductive consequences of menopause with particular consideration of the occurrence of visceral obesity, insulin resistance, hyperinsulinaemia, arterial hypertension, glucose metabolic disorders, increased development of atherosclerosis and its cardiovascular complications. It should be emphasized that the latest studies have demonstrated that menopause is beside body mass index (BMI), triglyceride level and LDL level an independent risk factor of increased fasting glycaemia, even in non-diabetic women. Thus, it seems that in menopausal women, due to a significant increase of cardiovascular risk, education should play a particularly important role, considering healthy lifestyle and ischaemic heart disease primary prevention by modification of risk factors: normalization of body mass index, lipid profile, blood pressure and glycaemia control.